Development and piloting of 'When Cancer Comes Along': A cancer awareness program for Australian secondary school students. (27th December 2019) - Wright, Adam J.; Patterson, Pandora; McDonald, Fiona E. J.; Hubbard, Gill
Abstract: Issue addressed: Given the increasing prevalence of cancer, there is a growing need for health interventions educating individuals about the disease and its impacts, risk‐reduction strategies and how to support others who are affected. School‐based programs are a promising medium addressing these issues in adolescents, yet no comprehensive cancer education program exists in Australia. This paper reports on the piloting of a cancer awareness program for Australian students. Methods: When Cancer Comes Along is a 90‐minute interactive presentation covering cancer's impacts, risk‐reduction strategies and how to support those affected. The program was piloted in four Australian secondary schools, with students (N = 113, 13‐16 years) and teachers (N = 2) providing feedback via postprogram survey. Results: Participants reported high satisfaction overall (92%‐97%) and with each program component (71%‐95%), and agreed that the program achieved learning outcomes (72%‐95%). Conclusions: Results indicate that When Cancer Comes Along is relevant, engaging and age‐appropriate. Participants reported improved understanding of cancer, its impacts, risk‐reduction strategies and how to support those affected. A larger‐scale evaluation is underway to more comprehensively evaluate program outcomes. So what?: The program has potential in educating students about various aspects of the cancer experience. It further demonstrates the feasibility and value of addressing psychosocial impacts and support strategies as well as information about cancer risks, elements which have not previously been combined in educational interventions. Equipping adolescents with the knowledge and skills to reduce their cancer risk and support others who are affected has significant health promotion implications for cancer prevention and support provision. Summary: This paper describes the piloting of a cancer awareness program for high school students that addresses what cancer is, its impacts, risk‐reduction strategies and how to support someone affected by cancer. Participating students and teachers indicated high satisfaction, suggesting the program is relevant, age‐appropriate and effective in educating adolescents about cancer.